Figado cru, de suino com peste suina, como causa de um surto de cólera aviaria - Correa, O. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A group of fowl was fed with rough hog livers, contaminated with hog fever. As a result of this process, several chickens died and when an autopsy was practiced on them, the germ of Pasteurella multocida was isolated. The chicken that survived were inoculated with a solution of dehydrostreptomycin and they were given sulfquinoxalin in the drinking water. Shortly afterwards, few of the animals that were sick before the inoculation, died. In order to trace back the pathogenic germ, laboratory tests were carried out with pieces of the hog liver fed to the chickens; in successive cultures, Pasteurella multocida was isolated in the same manner that it was found in the chickens.